Women's 50km racewalking tactic using pace strategy analysis at World Championships - Megahed, M.; Ali, R.; Tarek, Z. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. We aim to design a walking tactic depending on pace strategy analysis for women's 50km racewalking at two IAAF championships: World Racewalking Team Championships Taicang2018 and World Athletics Championships Doha2019.Material and Methods. We collected data from the records of the women's 50km racewalking results from both mentioned championships in which the times of 10 stages of 5km each. The research sample included 30 racewalkers (top 15 from each championship) aged 21 to 41. Results. Results indicate that elite racewalkers followed a variable pace strategy. As they started a 50km racewalking with a slow and appropriate speed. Then there was a gradual increase in the next stages until reaching the speed plateau (25km). After that, the speed was changed between increasing and decreasing until the end of the race. The results also indicate that there is a strong positive correlation between the performance time of all the stages in both championships. In addition, it is indicated that there are statistically significant differences using the T-test between all stages between both championships, except for the stage (10th 5km). So last 5km have no major impact on changes for the final classification. Conclusions. We divided the race into seven successive tactical phases depending on the speed and the effort rate during the race stages. These phases are slow start, primary acceleration and speed regulation, the maximum speed, transitional, final acceleration, deceleration, and finish. Our analysis can extend theoretical knowledge, so coaches and racewalkers can make use of it in designing the training programs.